Explaining dissolution properties of rivaroxaban cocrystals - Hriňová, Erika; Skořepová, Eliška; Čerňa, Igor; Královičová, Jana; Kozlík, Petr; Křížek, Tomáš; Roušarová, Jaroslava; Ryšánek, Pavel; Šíma, Martin; Slanař, Ondřej; Šoóš, Miroslav (International journal of pharmaceutics, 2022)
The aim of this study was to improve rivaroxaban water-solubility by cocrystal preparation and to understand this process. The screening with water-soluble coformers was performed via both mechanochemical and solution-mediated techniques. Two cocrystals of rivaroxaban with malonic acid and oxalic acid were prepared, and the structure of the cocrystal with oxalic acid was solved. Both cocrystals exhibit improved dissolution properties. The mechanism of the supersaturation maintenance was studied by in-situ Raman spectroscopy. The transformation into rivaroxaban dihydrate was identified as the critical step in the improved dissolution properties of both cocrystals. Moreover, the transformation kinetics and solubilization effects of the coformers were identified as responsible for the differences in the dissolution behavior of the cocrystals. In-vivo experiments proved that the use of cocrystal instead of form I of free API helped to increase the bioavailability ofrivaroxaban.
Keywords: voda; In-vivo studies; Solid form transformation; Oxalic Acid; kyselina oxalová; Dissolution; Rivaroxaban; X-Ray Diffraction; Crystallization; Cocrystal; Water; Solubilization; difrakce rentgenového záření; krystalizace; Solubility; rivaroxaban; rozpustnost